The discourse of inclusivity in children’s literacy advocacy communities in East Java - Ghanesya Hari Murti; Ni Luh Ayu Sukmawati; Andang Subaharianto; Ayouvi Poerna Wardhanie (Priviet Social Sciences Journal, 2026)
Bullying remains a pervasive issue in schools and communities, signaling a need for learning environments prioritized around human connection rather than rigid discipline. In the empirical setting of East Java, local literacy initiatives such as TBM_Segenteng (2025), Read Aloud Malang Raya, and Sekolah Sastra Anak are pioneering spaces in which narrative engagement fosters empathy and global awareness. This study adopts a qualitative discourse-analytic approach grounded in Foucault’s (1972) discourse theory to examine how children’s literature functions as a transformative pedagogical tool. Rather than treating inclusivity as a static normative ideal, the findings demonstrate how inclusivity and anti-discriminatory attitudes are discursively produced through the shared practices of reading and collective discussion. By documenting these community-based literacy activities, the research shows that curated narratives encourage diverse character development and social responsibility. Ultimately, the paper contributes to the field by illustrating how the deliberate production of diverse children’s books and literacy practices can actively dismantle discriminatory structures in young readers.